Counseling and therapy for couples - Long, Lynn L. (Thomson Brooks/Cole, 2007)
From the Publisher: Long and Young's text presents a broad view of the developing field of couples counseling, offering extensive coverage of virtually every aspect of its principles, evaluation, planning, treatment strategies, and challenges. In the text, the authors propose a single structure that brings together the field's major theoretical viewpoints. They present the integrative model within an atheoretical context in which many types of couples are addressed-heterosexual, same-sex, culturally mixed, married, and unmarried-thus ensuring that readers are fully prepared to work with various types of clients.